Social exclusion among peers: The role of immigrant status and classroom immigrant density. - Plenty, S; Jonsson, JO (Springer, 2016)
Increasing immigration and school ethnic segregation have raised concerns about the social integration of minority students. We examined the role of immigrant status in social exclusion and the moderating effect of classroom immigrant density among Swedish 14-15-year olds (n = 4795, 51 % females), extending conventional models of exclusion by studying multiple outcomes: victimization, isolation, and rejection. Students with immigrant backgrounds were rejected more than majority youth and first generation non-European immigrants were more isolated. Immigrants generally experienced more social exclusion in immigrant sparse than immigrant dense classrooms, and victimization increased with higher immigrant density for majority youth. The findings demonstrate that, in addition to victimization, subtle forms of exclusion may impede the social integration of immigrant youth but that time in the host country alleviates some risks for exclusion.